Overview of Business Tourism During Covid-19 Pandemic - Abdo KATAYA (Communications of International Proceedings, 2021)
Business tourism represents the main niche in the destination tourism market, employing millions of people and representing. Business tourism includes trips and visits made by employees during their activity, being very diversified, which makes it difficult to generalize the main characteristics of its products. One of the advantages of business travel is that they are less seasonal than leisure tourism. Despite the growing interest in innovation, there is an incomplete understanding of how innovation processes take place in tourism businesses and organizations and their impact on destinations, as well as entities involved in business tourism. Society as a whole is facing an unprecedented level of economic, political and environmental unrest. As a result, the present, especially the future of the business tourism, constitutes a complex and diversified challenge. This paper investigates the benefits of business tourism and the impact of the Covid-19 pandemic effects on this industry. Travel restrictions and social isolation measures imposed by governments around the world in an attempt to stop the spread of coronavirus are severely affecting global tourism, from small businesses to large hotel chains or tour operators. The present situation is likely to result in the creation of new corporate policies governing business travel.
Keywords: business tourism; Covid-19 pandemic; economic growth; globalization; tourism market